Psicanalise e educação escolar: contribuições de Melanie Klein - Almeida, Alexandre Patricio de (2018)
Much is discussed about the contributions of psychoanalysis to the most diverse areas of knowledge. Freud was able to produce a science that could rethink the formation and the constitution of a subjective knowledge, focused on the essence of the subject and the affective relations that surround it. The school is a great example of this paradigm. It is in school that many children spend most of their time learning to deal with external conflicts in an attempt to mature their own inner struggles. This interiority was so well explored by Melanie Klein. Its vast theoretical framework, based on the exploration of the infantile inner world and its respective constitutive fantasies, is a great watershed for the understanding of the human being within psychoanalytic epistemology. This research will start from the experiences of the author as an educator and clinical psychoanalyst, in an attempt to articulate the kleinian concepts to the emotional situations witnessed in this professional and personal journey. It is not an instruction manual on how to put Melanie Klein s theory into practice, but rather a broad understanding of its general concepts in order to facilitate an understanding of the complex affective situations that permeate the field of school education. Given the character of this dissertation, there is no way to present closed conclusions, but rather to open the way to educational practices that follow an ethics of the subject, considering children and educators as subjective beings, consisting of emotional experiences, irremediably incomplete and with a character incredibly broad and comprehensive that can not (and should not) be simplified by a theory that sees it simplistically